(untitled) (Research, Society and Development, 2021)
Duchenne Muscular Dystrophy (DMD) is an inherited, autosomal recessive X-linked disease, affecting mainly males. There is progressive muscle impairment, starting with the proximal muscles of lower limbs, then reduction of upper limbs muscle strength and impairment of cardiac and respiratory muscles, with no curative therapy. Thus, this is a case report of a patient with Duchenne Muscular Dystrophy, emphasizing the possible endocrinological effects that can manifest in this pathology. The best medication for the management of Duchenne Muscular Dystrophy is corticosteroid, which improves muscle strength, extending gait time, preserving the function of upper limbs, preventing scoliosis, reducing cardiomyopathy progression and delaying invasive ventilation need. However, this medication offers a range of adverse effects to these patients, making endocrinological care necessary, with the following objectives: monitoring growth, pubertal development, diagnosing hormonal deficiencies, providing replacement therapy when necessary and preventing the occurrence of adrenal crisis.